2016
DOI: 10.1080/08997659.2016.1150907
|View full text |Cite
|
Sign up to set email alerts
|

Quorum Signal Inhibitors and Their Potential Use against Fish Diseases

Abstract: Quorum sensing (QS) is a process of bacterial communication used to control group behaviors, including bioluminescence, virulence factor production, biofilm formation, and biofilm antimicrobial tolerance. Many aquatic bacterial pathogens such as Aeromonas, Vibrio, and Edwardsiella spp. use QS to regulate virulence factor production. The disruption of QS has been shown to be an effective strategy in the competition between higher organisms and bacteria and more recently between bacterial species. For this reaso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…In addition, uptake of substances such as propidium iodide or N -phenyl-l-napthylamine indicates that formation of unregulated pores in the membrane and an increased probability of cell death. Finally, cell-to-cell communication among bacteria (quorum sensing), used to control group behaviors, including virulence factor production or biofilm formation, is another central target that could help to reduce antimicrobial resistance [ 46 ].…”
Section: Mechanisms Of Essential Oil Cytotoxicitymentioning
confidence: 99%
“…In addition, uptake of substances such as propidium iodide or N -phenyl-l-napthylamine indicates that formation of unregulated pores in the membrane and an increased probability of cell death. Finally, cell-to-cell communication among bacteria (quorum sensing), used to control group behaviors, including virulence factor production or biofilm formation, is another central target that could help to reduce antimicrobial resistance [ 46 ].…”
Section: Mechanisms Of Essential Oil Cytotoxicitymentioning
confidence: 99%
“…luxS is responsible for the production of AI-2 QS signal molecules, commonly referred to as AI-2 molecules [ 57 ]. As previous studies revealed that the luxS isogenic mutant of A. hydrophila altered biofilm formation dynamics and its architecture, bacterial motility reduced and virulence has been enhanced observed in a mouse model [ 58 ] and luxS mutant strain failed to produce AI-2 as studied in Aeromonas salmonicida [ 59 ] Another report shows that tannic acid is also a potential QS inhibitor, which reduces biofilm formation, swarming motility and blood haemolysis activity of fish pathogenic bacteria [ 60 , 61 ]. Moreover, 5906 a small peptide binds with Luxs and prevents the synthesis of functional LuxS homodimer of Edwersilla tarada [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…Quorum quenching is the process of disrupting quorum sensing, that is a mode of social life communication among microbes dependent on cell density that regulates a plethora of behaviours, including virulence in many aquatic pathogens such as Aeromonas , Vibrio and Edwardsiella (Chu & McLean, 2016). Quorum sensing inhibitors are synthetic or natural molecules that interfere and disrupt this communication mechanism.…”
Section: Changes In the Selective Context Along The Production Chainmentioning
confidence: 99%
“…Given the complexity of live cultures, an alternative option is to directly use the molecular compounds. Some authors advocate the search for these invariant microbiota‐harnessing tools as alternative antimicrobials, like quorum sensing inhibitors (Chu & McLean, 2016) and bacteriocins (Sahoo et al., 2016). In food, compounds that underlie spoilage are often under the control of quorum sensing mechanisms.…”
Section: Microbial Community Modulation Strategies From Egg To Fork: mentioning
confidence: 99%